The Migration Experience of Highly Skilled Ghanaians under the Canadian Federal Skilled Worker Program to Canada - Addy, A.A.N. (University of Ghana, 2019)
The purpose of this research was to examine the migration experience of the highly skilled Ghanaians who migrated to Canada through the Federal Skilled Worker Program (FSWP). The study particularly seeks to find out the expectations of participants before emigration, their experiences as they attempted to participate in sectors for which they gained admission into Canada. The study was done in “multiple sites” in Canada: Ontario, British Columbia and Alberta Provinces and in Accra, Ghana. The qualitative research method approach was adopted for the study. Data were collected through in-depth face to face interviews and telephone interviews from twenty-one participants. Secondary (statistical) sources and information were also used in exploring some of the research objectives. The Dual Labour Market theory, the Neoclassical theory, the Network theory of migration by Massey et al (1997) and the Forms of Capital theory by Bourdieu (1986) provided a theoretical foundation for the understanding of the migratory process, general settlement and integration process of the highly skilled Ghanaian immigrants in Canada. The study found that the participants had multiple expectations prior to migrating. The desire to be legally resident outside their home country (Ghana) was the primary reason for the majority. All the participants arrived in Canada as landed permanent immigrants. After three years, most of them attained the status of a Canadian national and were holding a Canadian passport. Being Canadians, they were accorded all the rights and privileges of a native-born in Canada. They were also allowed to travel to other Organisation for Economic Cooperation and development (OECD) countries without any difficulty of acquiring visas and the limitations of most immigration laws as in the case when one travels on a Ghanaian passport. Another expectation of the participants was to enter into the labour market with their occupations and skills. This expectation was not fulfilled for many of them. They faced barriers as they attempted to enter sectors for which they had qualified through the FSWP. The main barriers found were lack of Canadian experience, devaluation of their credentials, racism, discrimination and psychological issues. To overcome these barriers, the participants adopted strategies such as volunteering, furthering their education, downgrading their qualifications or skills, changing careers altogether and, moving into unregulated sectors of employment. They had to deal with the feelings of emotional distress, anxiety and disruption of their families by making sense of their difficulties through the idea of sacrifices that they had made, often for their children. They also adapted to their new lives in Canada by compromising, seeking information and seeking comfort in love and support of family and religion. Recommendations made were that there should be Synchronization between various levels of governments and offices responsible for the labour market to overcome the disjoint between the Federal Skilled Worker Program (FSWP) policies and the labour market opportunities on a structural level, Credentialing process to assess foreign skills and educational certificates should be standardized. It was also recommended that there should be an introduction of mentorship programmes for the immigrants to solve issue of lack of information as well as the introduction of extensive bridge training programs should be organized to help skilled newcomers get their license or certificate in their profession to address the issue of brain waste. Counselling should be provided for new immigrants and families to help deal with and overcome psychological and emotional barriers of settlement and integration and to alleviate some illnesses and challenges that are associated with migration
PhD. Migration Studies.
Keywords: Migration Experience; Federal Skilled Worker Program (FSWP); Canada